INVESTIGATING LINKAGES OF PERFORMANCE APPRAISAL, EMPLOYEE PROMOTION AND JOB SATISFACTION WITH EMPLOYEE PERFORMANCE IN BANKING SECTOR OF PAKISTAN - Kibria, Aamir; Kazi, Dr. Abdul Subhan; Banbhan, Dr. Ashfaque Ali; Shahani, Akram Khan; Junejo, Ikramuddin (The journal of contemporary issues in business and government, 2021)
This research investigated the association between performance appraisal, employee promotion job satisfaction with employee performance in the banking sector of Pakistan. The SEM analysis approach was utilized in Smart PLs on 280 samples of bank officers. It has been revealed by the results that performance appraisal has a constructive relationship with employee promotion, satisfaction, and performance. Moreover, rewards and appreciations are not based on the number of tasks or workload. Additionally, research explicated and expressed the worthiness of human resource practices from the perspective of the private banking sector of Pakistan. The research implications suggest that authorities of private banks must pay significant attention to recognition and reward practices as workers expecting rewards accordingly to their efforts.